Analysis of influencing factors on postoperative complications of closed approach autologous granular rib cartilage rhinoplasty and construction and verification of nomogram - Ju, Ye; Wang, Jinlei; Shi, Xiaohong; Chi, Wentao; Zhan, Chenguang (Frontiers in Surgery, 2025)
ObjectiveTo construct a nomogram prediction model based on the risk factors of complications after augmentation rhinoplasty with autogenous granular costal cartilage through closed approach, and to explore its clinical application value.MethodsFrom June 2022 to June 2024, 214 patients in our hospital were selected and divided into training set (n = 150) and verification set (n = 64) according to the ratio of 7:3. In the training set, the risk factors of postoperative complications were analyzed by multivariate Logistic regression, and then the nomogram prediction model was constructed. The prediction efficiency of the model is evaluated by drawing ROC curve and calibration curve, and verified in the verification set. The decision curve analysis (DCA) was used to evaluate the clinical application value of the model.ResultsComplications occurred in 31 cases (20.67%) in the training group and 13 cases (20.31%) in the verification group. There was no significant difference in the incidence and clinical characteristics between the two groups (P > 0.05). In the training set, older age, history of chronic diseases (chronic rhinitis), long operation time, large amount of bleeding during operation and thin skin on the back of nose were independent risk factors for complications (P < 0.05), and a nomogram prediction model was established accordingly. The model has good calibration and fitting degree in training set and verification set (C-index index is 0.857 and 0.848, average absolute error is 0.126 and 0.090, and χ2 of Hosmer-Lemeshow test is 7.137, P = 0.521 and χ2 = 5.923, P = 0.655). The ROC curve shows that the AUC of the training set and the validation set model for predicting postoperative complications are 0.851(95% CI: 0.764–0.937) and 0.855(95% CI: 0.675–1.000), and the sensitivity and specificity are 0.880, 0.725, 0.833 and 0.692, respectively.ConclusionThe nomogram prediction model based on risk factors is helpful for early prediction of complications after augmentation rhinoplasty, providing guidance for clinical decision-making, helping to reduce the risk of complications and improving the surgical effect and patient satisfaction.